PENGUKURAN MINAT MAHASISWA BERDASARKAN TEORI HOLLAND - Iriani Indri Hapsari; Herdiyan Maulana (Perspektif Ilmu Pendidikan, 2013)
This research aims to explore the students’ interestat the School of Education, State University of Jakarta. The interest model was based on Holland interest theoritical framework. Descriptive analysis was used to analyze the data from eight dapartments at school of education. The respondents involved 200 students from 2008 to 2011 recruitment. The data were collected through purposive nonrandom sampling technique. The results show that majority of respondents have entepreuners interest, then social, and realistic interest the fewest. The result shows that majority interest of FIP students matches with their academic background.